EVALUATION OF LIVING STANDARDS IN RURAL AREAS IN THE REPUBLIC OF MOLDOVA - Silvia ZAHARCO (Economy and Sociology, 2015)
Actuality. this paper presents a characterization of living conditions of the population from the national rural areas. The study of rural development is conditioned by the need to signal particularly acute social and economic problems faced by the people living in rural areas. Objective: Identification the determinant factors of rural poverty and to highlight measures to improve the living standards of the rural population. Methods: The investigation was conducted using the monographic method, the study is focused on a well-defined social field. Results: The standard of living in rural areas is in a continuous decline, there is a trend of population aging and the depopulation of villages is caused by the migration process. Promoting a realistic policy of improving living conditions in rural areas, changing attitudes towards the village, raising the prestige of the farmer is absolutely appropriate to improve the socio-economic and cultural development of the country.